2014
DOI: 10.1136/bcr-2013-202084
|View full text |Cite
|
Sign up to set email alerts
|

Antenatally detected solid tumour of kidney

Abstract: Congenital renal tumours are rare and usually benign. Polyhydramnios is the most common mode of presentation. Although most cases have been diagnosed postnatally, with advances in imaging technology, an increasing number of cases are being detected on antenatal scans. We describe a case of solid tumour of kidney detected in the second trimester of pregnancy and managed by surgery in the postnatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Antenatally detected renal tumours are usually associated with the sonographic findings of polyhydramnios and hydrops fetalis, and can present with acute fetal distress. Polyhydramnios is the most common complication,7 and was seen in our case. Hydrops is not commonly described but can occur due to compression of the infra-diaphragmatic vessels, namely the IVC and the ductus venosus.…”
Section: Discussionsupporting
confidence: 59%
“…Antenatally detected renal tumours are usually associated with the sonographic findings of polyhydramnios and hydrops fetalis, and can present with acute fetal distress. Polyhydramnios is the most common complication,7 and was seen in our case. Hydrops is not commonly described but can occur due to compression of the infra-diaphragmatic vessels, namely the IVC and the ductus venosus.…”
Section: Discussionsupporting
confidence: 59%
“…Reports from Leclair et al showed that 39% of fetal renal tumors had polyhydramnios as the main perinatal complication ( 23 ). Other reported complications include hypercalcemia, intra-tumoral hemorrhage, and non-immune hydrops fetalis leading to prematurity, fetal distress, and fetal demise ( 29 ). Our review of the data showed that the survival rate is excellent for infants who had isolated fetal WT, except for one patient who had disease progression secondary to therapeutic delays and suboptimal management leading to death ( 12 ) and another fetus that had several malformations that could be related to a syndrome and can explain the early mortality ( 14 ).…”
Section: Discussionmentioning
confidence: 99%